Household and plot level impact of Sustainable Land and Watershed Management (SLWM) practices in the Blue Nile - Schmidt, Emily; Tadesse, Fanaye (International Food Policy Research Institute, 2012)
Land degradation and water shortages are major issues in developing countries, contributing to reduced economic output, lower growth potential and increased poverty. The immediate trade-off between short-term welfare and long-term agricultural development in the highland regions of Ethiopia represents a challenge to successful economic development in a predominantly agricultural-based economy. Although previous studies investigated countrylevel economic costs of sustainable land and watershed management (SLWM) in Ethiopia, few quantitative assessments of household level SLWM adoption and maintenance, linked to benefit payoff horizons and magnitude, exist in recent literature. We employ nearest-neighbor matching techniques to measure the impact of adopting specific SLWM technologies on value of production. Results suggest that households that adopted terraces, bunds, or check dams within the first period of the study period (1992– 2002) experience a 15.2 percent higher value of production in 2010, while late adopters (farmers that adopted SLWM between 2003–2009) have no significant increases in value of production.